Population Sorting and Human Capital Accumulation - Leonid V. Azarnert (Center for Economic Studies and ifo Institute (CESifo), 2021)
This article analyzes the effect of population sorting on economic growth. The analysis is performed in a two-region growth model with endogenous fertility, in which public knowledge spillovers from the more advanced core into children's human capital accumulation function in the periphery are incorporated. I show how migration affects the inter-temporal evolution of human capital in each of the regions and the economy as a whole. I also discuss how public policy interventions can help increase the per-capita human capital levels, if free uncontrolled migration leads to a reduction in human capital accumulation.
Keywords: D30; J10; O15; O18; 330; migration; population sorting; knowledge spillovers; fertility; human capital; economic growth